Tārīḫ ʿUṯmān Ibn-Saʿīd ad-Dārimī 200-280h ʿan Abī-Zakarīyā Yaḥyā Ibn-Maʿīn al-Baġdādī (158-233h) fī taǧrīḥ ar-ruwāh wa-taʿdīlihim - Dārimī, Abū-Saʿīd ʿUṯmān Ibn-Saʿīd ad-,Azharī, Abū-ʿUmar Muḥammad Ibn-ʿAlī al- (al-Fārūq al-Hadīṯa li-ṭ-Ṭibāʿa wa-'n-Našr, 2008)
Hadith; authorities; early works to 1800
Ersch.-Jahr 1429h
Keywords: Wörterbuch